Training with ropes and rubber according to the direction of the movement and its impact on some of the steps biomechanical variables recent upgrading and completion of the long jump for youth - Najim, Jamela (Journal of Physical Education, 2019)
The use of training aids that force athlete to break the usual pattern when it moves the application of the maximum speed and explosive power and fast things became effective training in influencing the development of speed in the final steps of the players, the long jump. So she wanted a researcher to develop this speed using ropes rubber towards the movement to strengthen the tracks motor during the performance of the final steps to get closer and upgrading, which is one of the most important problems of these competitions with the integration of mechanical performance, particularly during the last steps and upgrading and thus achieve the feat good associated with this development. The goal of the research is to identify some of the biomechanical variables and recent steps to improve the long-Jump youth. Preparation and special training in using ropes rubber positive direction of the movement for the development of biomechanical variables special steps recent upgrading and achievement. And applied research on a sample of Athby the long jump at 12, was filmed sample during the recent steps and approach to extract the variables speed approaching and cruising speed and change the momentum for takeoff and achievement after being hit by the group to exercise science by using rubber cords according to the paths body parts during the performance, and the results Find that evolved approach speed and cruising speed - change momentum during the upgrading and development of achievement clearly